Aplicación del enfoque de la gestión por procesos de una lacto planta en la Provincia de Santo Domingo de los Tsáchilas - Espinoza Torres, Luis Alberto (2011)
It has been considered Process Management is the appropriate mechanism to obtain a significant improvement in LEFRIDERSA SA, ie understand their procedures, performance and needs that allow understanding the needs of its members, the Commitment is the foundation, to analyze the enterprise as a system in which parts so that direct their efforts towards achieving a common goal, getting numerous qualitative and quantitative benefits interact.